Histone deacetylase inhibitors in the treatment of cancer: overview and perspectives. (July 2012) - Giannini, Giuseppe; Cabri, Walter; Fattorusso, Caterina; Rodriquez, Manuela
Histone deacetylase inhibitors (HDACis) are one of the last frontiers in pharmaceutical research. Several classes of HDACi have been identified. Although more than 20 HDACi are under preclinical and clinical investigation as single agents and in combination therapies against different cancers, just two of them were approved by the US FDA: Zolinza ® and Istodax ®, both licensed for the treatment of cutaneous T-cell lymphoma, the latter also of peripheral T-cell lymphoma. Since HDAC enzymes act by forming multiprotein complexes (clusters), containing cofactors, the main problem in designing new HDACi is that the inhibition activity evaluated on isolated enzyme isoforms does not match the in vivo outcomes. In the coming years, the research will be oriented toward a better understanding of the functioning of these protein complexes as well as the development of new screening assays, with the final goal to obtain new drug candidates for the treatment of cancer.